Rozkłady fazowe i ich zastosowanie do wyznaczania prawdopodobieństwa ruiny ubezpieczyciela - Jasiulewicz, Helena (Phase-Type Distributions and Their Application to Calculating the Insurer's Ruin Probability, 2006)
In the paper the phase-type distributions were defined by Markov processes. The properties of the distributions and convolutions and mixtures of those distributions were discussed. Applications to determine ruin probability were given.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (17); 2006; nr 1123, s. 217-231